Zircon U-Pb geochronology and petrogenesis of metabasites from the western Beihuaiyang zone in the Hong'an orogen, central China: Implications for detachment within subducting continental crust at shallow depths. (1st September 2017) - Liu, Yi-Can; Liu, Li-Xiang; Li, Yuan; Gu, Xiao-Feng; Song, Biao
Graphical abstract: Highlights: The low-grade metabasites in the Dabie orogen formed at ∼750 Ma and ∼630 Ma. The metabasites underwent epidoteamphibolite facies metamorphism at ca. 240 Ma. A case study for detachment within the subducted crust at shallow depths. Abstract: Deformed low-grade metabasites from the western segment of the Beihuaiyang zone in the Hong'an orogen, central China can be divided into two types, i.e. meta-gabbro and meta-basalt. These lithologies have been studied by using whole-rock elemental and Sr-Nd-Pb isotopic analyses, and zircon SHRIMP U-Pb dating. Concordant zircon U-Pb ages of 631 ± 5 Ma and 623 ± 14 Ma are obtained for the meta-gabbros, consistent with a previously reported U-Pb age of 635 ± 5 Ma. The meta-basalt was dated to have a protolith age of middle Neoproterozoic (∼750 Ma) and a metamorphic age at ca. 240 Ma. The all studied metabasites occur as block or slice within a metamorphosed Ordovician volcanic zone (originally named as the Dingyuan Formation) and are in tectonic contact to each other. The gabbro and basalt emplaced at ∼630 Ma and ∼750 Ma, respectively in a continental rifting setting, whereas their present country rocks were erupted at ∼465 Ma in an arc setting. The Pb-isotope compositions of the low-grade meta-gabbros and meta-basalts are similar to those from the Dabie ultrahigh-pressure (UHP) meta-igneous rocks with an upper continental crust affinity. The protolith ages of the studied relatively low-grade meta-basic rocks are in good agreement not only with ages for two episodes of middle and late Neoproterozoic mafic and felsic magmatism in the Suizhou to Zaoyang areas at the northern margin of the South China Block, but are also in agreement with the protolith ages of UHP meta-igneous rocks in the Dabie-Sulu orogenic belt. Therefore, these Neoproterozoic low-grade metabasites are considered to be exotic and they may have been detached and offscraped from the subducting upper crust of the South China Block at shallow depths during continental collision in the Triassic. They were subsequently exhumed in the initial stage of continental subduction, and thrusted over the Paleozoic metamorphosed rocks in the southern margin of the North China Block or as foreign slices within the UHP metamorphic zone. They are a kind of the accretionary wedge involved in the Paleozoic oceanic subduction, and Triassic crustal detachment and tectonic overthrusting during the early stage of continental subduction.